The effect of changes in hitting location on bat-swing parameters in baseball batting - Morishita, Y.; Katsumata, Y.; Jinji, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The purpose of the present study was to clarify the influence of swing parameters by changing the hitting point in space in baseball batting. Twenty-eight skilled baseball players (12 professional and 16 universitylevel) participated. The participants were instructed to hit a ball that was tossed from 5 m away in the direction of the pitching mound. The balls were tossed to various locations with reference to the home plate. The participants were required to hit the balls in a specific direction according to the tossed course, i.e., a ball tossed to the inside of a home plate was stroked toward the same-field direction and one tossed outside of the home plate was stroked toward the opposite-field direction. The motions of the ball and bat during these attempts were recorded using a motion capture system operating at 500 Hz. The 3D coordinates of the ball center (hitting point) and the swing parameters included the speed of the head of the bat (bat-head speed) and the angle of the swing from a horizontal line (swing angle) measured immediately before ball impact and the time from the start of the swing to ball impact (swing time). These parameters were calculated in each trial. Analysis of a total of 644 trials revealed that the bathead speed tended to increase as the hitting point moved inside, forward, and low. Furthermore, the swing angle and swing time tended to increase as the hitting point moved inside, forward, and high. Stepwise multiple regression analysis demonstrated that the bat-head speed and swing angle were independently associated with (in the following order) the distance in the pitcher`s direction, the hitting height, and the inside-outside direction course (R2=.360 and R2=.589, respectively). These results suggest that the timing of swing initiation and bat acceleration during a swing motion are the main factors changing the swing parameters, and that in order to sharp hit a ball, it is important to impact the ball with the hitting point as close to the pitcher as possible.